2021
DOI: 10.1111/jfpp.15766
|View full text |Cite
|
Sign up to set email alerts
|

Investigation effects of inulin degree of polymerization on compound chocolate quality

Abstract: This is the first study in which the effect of degree of polymerization (DP) (˂10 and ≥23) of inulin (6.00, 9.00, and 12.0/100 g) on main quality parameters (color, texture, water activity, sensory properties, and melting behavior) of compound chocolate's (CC) was investigated. According to the determined L* values, using inulin (12/100 g) with high DP resulted in more glossy samples (p < .05). Except ∆h value, the melting parameters of CC were not affected. However, the hardness of samples (391.9–587.1 g) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…The differences in textural parameters were attributed to the differences in the particle size, moisture content, total solid content, and interactions of particles in the samples. In a study, Goktas et al (2021) prepared compound chocolate by replacing sugar with inulin (6–12%) having different polymerization degrees (DP <10 and DP ≥23) and reported that the hardness of compound chocolate was affected by both the polymerization degree and the level of inulin in formulation. Sample containing 6% inulin with low DP had the lowest firmness while sample containing similar amount of inulin with high DP produced the highest firmness in their study.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in textural parameters were attributed to the differences in the particle size, moisture content, total solid content, and interactions of particles in the samples. In a study, Goktas et al (2021) prepared compound chocolate by replacing sugar with inulin (6–12%) having different polymerization degrees (DP <10 and DP ≥23) and reported that the hardness of compound chocolate was affected by both the polymerization degree and the level of inulin in formulation. Sample containing 6% inulin with low DP had the lowest firmness while sample containing similar amount of inulin with high DP produced the highest firmness in their study.…”
Section: Resultsmentioning
confidence: 99%
“…The melting characteristics of WSPC were assessed by using a differential scanning calorimeter (DSC 220 F3-Netzsch, USA). A chocolate sample weighing 3 ± 0.2 mg was placed in a tightly sealed aluminum pan and subjected to heating from 25 to 100 °C in a nitrogen stream at a rate of 5 °C per minute …”
Section: Methodsmentioning
confidence: 99%
“…A chocolate sample weighing 3 ± 0.2 mg was placed in a tightly sealed aluminum pan and subjected to heating from 25 to 100 °C in a nitrogen stream at a rate of 5 °C per minute. 33 2.8.3. Rheology.…”
Section: Melting Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation